Trust and satisfaction towards loyalty business mediated with relationship quality with a turbulent environment in East Java sugar cane farmers B2B sector (Journal of Social Economics Research, 2025)
This paper discusses the effects of trustworthiness, business loyalty (BL), perseverance, and relationship quality (RQ) on environmental volatility (ET). Assessment of a Likert-scale survey questionnaire was conducted to analyze the average value for each item, indicator, and variable in a descriptive manner. Data collection was done via a manual sample survey. Analyzed data using Structural Equation Modeling (SEM) on Smart PLS (partial least squares) 3.0. The study's findings indicate that while it has both a short- and long-term impact on loyalist business operations, it has a greater impact on long-term business operations with high-quality connections and short-term business operations with a fluctuating environment. The research findings demonstrate a direct correlation between trustworthiness and the quality of business-to-business and loyalty relationships. This is a result of the sugarcane farmer's relatively low level of trustworthiness when it comes to consistently reporting the results to the sugar plant; this is caused by the relatively low quality of the partnership.